Transcutaneous blood gas monitoring among neonatal intensive care units in Japan. Issue 2 (16th February 2020) - Ochiai, Masayuki; Kurata, Hiroaki; Inoue, Hirosuke; Ichiyama, Masako; Fujiyoshi, Junko; Watabe, Shinichi; Hiroma, Takehiko; Nakamura, Tomohiko; Ohga, Shouichi
Abstract: Background: This study aimed to investigate the utility of transcutaneous (tc) measurements of partial pressure of oxygen (tcPO2 ) and carbon dioxide (tcPCO2 ) monitoring in neonatal intensive care units (NICUs) in Japan. Methods: At the end of 2016, we sent a survey questionnaire on tc monitoring to all 106 NICUs registered with the Japanese Neonatologist Association. The questions included usage, subjects, methods, management, and the practical usefulness of tc monitoring. Results: The questionnaire was returned by 69 NICUs (65.1% of response rate). Seventeen institutions (24.6%) measured both tcPCO2 and tcPO2, and 42 (60.9%) measured tcPCO2 alone. Transcutaneous PCO2 or tcPO2 monitoring was applied for "pre‐viable" infants born at 22–23 weeks' gestational age (18.6% vs 23.5%), and infants of <500 g birthweight (30.5% vs 17.6%). The tcPCO2 and tcPO2 monitoring was started at birth in 49.2% and 70.6% of the newborn infants, respectively. The temperature of the sensor was set at <38°C for tcPCO2 in 54.3% and >42°C for tcPO2 in 58.9% of NICUs. The accuracy for tcPO2 was rated as good in 35.3% or moderate in 64.7%, of institutions but or for tcPCO2 as 1.7% or 93.2%of institutions, respectively. Conclusion: Transcutaneous monitoring was widely, but limitedly, used for preterm infants. The lower temperature of the tcPCO2 sensor compared to that reported in other developed countries might compromise the accuracy but increase the feasibility of tc monitoring in Japan.